Reconstruction Of The Use Of Library Information Services Through The Habitus Bourdieu Lens - Rihal, Henky Ahmad (AJIRSS: Asian Journal of Innovative Research in Social Science, 2025)
Although digital technology has made it easier for us to access knowledge, libraries now face real challenges to remain present in the hearts of the public. Behind the sophistication of online services, we still encounter the fact that interest in reading and physical visits to literacy spaces is still quite low, so libraries need to continue to improve so that they remain a lively and relevant place for human learning needs. This research touches on the human side in the academic world by exploring how a person's habits and social background affect the way he uses the library. Through Pierre Bourdieu's perspective, it is studied that access to knowledge is not just a matter of the availability of facilities, but is highly determined by life experiences, culture, and social networks that shape a person's behavior in learning. This research is qualitative with an exploratory and interpretive approach to systematic literature observation. Secondary data for this study, namely articles from empirical primary studies published in academic journals, conference proceedings, and related theses or dissertations. The results of the study show that the low number of visits to the library is actually rooted in deep social problems, where there is often a gap between people's living habits and the way libraries provide their services. In order not to feel unfamiliar, libraries must move from just a book provider to a welcoming and inclusive space for everyone with diverse backgrounds in their life stories. The future of libraries is no longer measured only by the sophistication of its facilities, but by its ability to embrace every individual to feel belonging and welcome in it.